Entrepreneurial orientation and open innovation in brazilian startups: a multicase study - Carvalho, Eduardo Gomes (2016)
Entrepreneurship and innovation are the basis to regional and national development. Therefore, entrepreneurs and startups are protagonists in this scenario. However, a new paradigm emerges in innovation studies: Open Innovation. But the relationship between Open Innovation and entrepreneurship is few explored. Thus, our work aims to fill this gap. Using case studies we check the hypotheses presented by Carvalho and Sugano (2016). At end, a framework and new hypotheses were presented to future studies.